The effect of job satisfaction on turnover intention among nurses at KPJ Johor Specialist Hospital / Hisyamuddin Sulaiman and Nur Syafeeka Zainudin - Sulaiman, Hisyamuddin; Zainudin, Nur Syafeeka (Faculty of Business and Management, 2015)
The shortage of nurses has become a worldwide issue. Consequently, nurses’ intention to leave has become a topic of great importance to researchers. Therefore, this study of intention to leave among nurses in KPJ Johor Specialist Hospital was conducted with four main objectives in order to achieve the purpose of this research. The first objective is to determine the level of job satisfaction. Second is to identify the level of turnover intention. Third objective is to identify the relationship between job satisfaction and turnover intention of nurses, and the last objective is to investigate which elements of job satisfaction namely as co – worker relationship, work environment, and salary level is most influence the turnover intention. In order to achieve all the four objectives, the quantitative research methods were used and the data were gathered by distributing 248 structured questionnaire to all the nurses at KPJ Johor Specialist Hospital. The data were analyzed by using Descriptive Analysis, Pearson Correlation Analysis, and Regression Analysis. The results indicates that there is a moderate level of job satisfaction and turnover intention that exists in KPJ Johor Specialist Hospital. The results revealed that there is significant moderate relationship between job satisfaction and turnover intention. The results also highlighted that co – worker relationship was the dominant element of job satisfaction in term of affecting the turnover intention, followed by salary level and work environment. The findings therefore were crucial to be looked into so that management and employers could have ample understanding and guidelines if they were to draft retention strategies. In conclusion, it shows that employees with high job satisfaction tend to have less intention to leave the organization compared to one with lower satisfaction towards his or her job. Hence, it shows that job satisfaction is an important element that influenced turnover intention among nurses in KPJ Johor Specialist Hospital.